The Consent Myth: Improving Choice for Patients of the Future - Charlotte A. Tschider (Washington University Law Review, 2019)
Consent has enjoyed a prominent position in the American privacy system since at least 1970, though historically, consent emerged from traditional notions of tort and contract. Largely because consent has an almost deferential power as a proxy for consumer choice, organizations increasingly use consent as a de facto standard for demonstrating privacy commitments. The Department of Health and Human Services and the Federal Trade Commission have integrated the concept of consent into health care, research, and general commercial activities. However, this de facto standard, while useful in some contexts, does not sufficiently promote individual patient interests within leading health technologies, including the Internet of Health Things and Artificial Intelligence. Despite consent’s prominence in United States law, this Article seeks to understand, more fully, consent’s role in modern health applications, then applies a philosophical-legal lens to clearly identify problems with consent in its current use. This Article identifies the principle issues with substituting consent for choice, the “consent myth,” a collection of five problems, then proposes principles for addressing these problems in contemporary health technologies.
Keywords: Consent myth; Patient choice; Health technologies; Privacy notices; HHS 2002 Privacy Rule; HIPAA; Patient consent; Choice-first privacy model